Pemeriksaan dan Edukasi Gangguan Pendengaran Pada Anak Panti Asuhan - Yolazenia Yolazenia; Asmawati Asmawati; Harianto Harianto (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Unhealthy ears may cause hearing loss. This issue may affect children to have difficulty communicating with others and decrease learning achievement at school. This community service activity aimed to give knowledge about hearing loss and conduct hearing examinations in orphanage children. This community service was held at the Aulia Al-Ikhlas Orphanage in Sungai Pagar Village, Kampar Kiri Hilir District, Kampar Regency, Riau. At the beginning of the activity, we provided counseling about hearing loss, followed by ear and hearing examinations using a tuning fork. Before and after the counseling, respondents filled out a questionnaire to assess knowledge about hearing loss. Twenty-four residents of the orphanage attended this activity. The questionnaires found that children's knowledge about hearing loss and ear health increased significantly after the counseling. The examination results found cerumen in 14 children, 4 with conductive hearing loss and 2 with sensory neural hearing loss. As a result, this community service activity can increase the knowledge of orphanage children about hearing loss and make their ears cleaner and healthier.